UPAYA MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) PADA MATERI BANGUN RUANG KELAS VIII SMPN 1 ENDE SELATAN TAHUN PELAJARAN 2018/2019 - Maria Lenika Rendas (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2020)
The problem occurs in SMPN 1 Ende Selatan is many students still get difficulties in mathematics and less of students' activity during the learning process. It causes the low of students' results in the study. That problem occurs because the teacher still uses the conventional method in the learning process. So, it makes students feel bored, and be passive. To overcome that problem, researchers apply the cooperative learning type Numbered Heads Together (NHT) to improve learning outcomes there are student activities. The type of research used is classroom action research with data collection techniques namely observation and tests. The learning process is carried out in stages, namely the planning, action, observation, and reflection stages. A series of stages are called cycles. This study occurred 2 cycles with the same implementation stages. Based on the result of data analysis, researchers concluded that classical completeness in cycles I was 56% and in cycles II was 92%. The observation results in observing student activities in learning cycles I was 66% and cycle II was 90%. Observation results in observing teacher activities in cycle I at 67% and in cycle II 92,72%. Therefore, the authors conclude that model cooperative learning type Numbered Heads Together (NHT) can improve learning outcomes and learning activities of class VIII of south Ende 1 Junior High School